A self-assembled dynamic extracellular matrix-like hydrogel system with multi-scale structures for cell bioengineering applications. (May 2023) - Xu, Yong; Rothe, Rebecca; Voigt, Dagmar; Sayed, Ahmed; Huang, Can; Hauser, Sandra; Lee, Pao-Wan; Cui, Meiying; Sáenz, James P.; Boccaccini, Aldo R.; Zheng, Kai; Pietzsch, Jens; et al.
Abstract: Extracellular matrix (ECM) provides various types of direct interactions with cells and a dynamic environment, which can be remodeled through different assembly/degradation mechanisms to adapt to different biological processes. Herein, through introducing polyphosphate-modified hyaluronic acid and bioactive glass (BG) nano-fibril into a self-assembled hydrogel system with peptide-polymer conjugate, we can realize many new ECM-like functions in a synthetic polymer network. The hydrogel network formation is mediated by coacervation, followed by a gradual transition of peptide structure from α-helix to β-sheet. The ECM-like hydrogels can be degraded through a number of orthogonal mechanisms, including treatments with protease, hyaluronidase, alkaline phosphatase, and calcium ion. As 2D coating, the ECM-like hydrogels can be used to modify the planar surface to promote the adhesion of mesenchymal stromal cells, or to coat the cell surface in a layer-by-layer fashion to shield the interaction with the substrate. As ECM-like hydrogels for 3D cell culture, the system is compatible with injection and cell encapsulation. Upon incorporating fragmented electrospun bioactive glass nano-fibril into the hydrogels, the synergetic effects of soft hydrogel and stiff reinforcement nanofibers on recapitulating ECM functions result in reduced cell circularity in 3D. Finally, by injecting the ECM-like hydrogels into mice, gradual degradations over a time period of one month and high biocompatibility have been shown in vivo . The contribution of complex network dynamics and hierarchical structures to cell-biomatrix interaction can be investigated multi-dimensionally, as many mechanisms are orthogonal to each other and can be regulated individually. Statement of significance: A list of native ECM features has attracted the most interest and attention in the research of synthetic biomaterials. In this research, we have described a simple ECM-like hydrogel system in which the complex and elegant functions of native ECM can be recapitulated in a chemically defined synthetic system. The ECM-like hydrogel systems were developed to avoid undesired features of biological substances (e.g., ethical concerns, batch-to-batch variation, immunogenicity, and potential risk of contamination), as well as gaining new functions to facilitate bioengineering applications (e.g., 3D cell culture, injection, and high stability). To this end, we have developed an ECM-like hydrogel system and provide evidence that this purely synthetic biomaterial is a promising candidate for cell bioengineering applications. Graphical abstract: Image, graphical abstract